INOVASI PENERAPAN APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL (IKD) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SAMBAS - Danil, Danil; Rahmadanita, Annisa (Institut Pemerintahan Dalam Negeri, 2024)
One way to accelerate the digitalization of public services is through digital population identity (IKD) innovation. However, in its implementation, the percentage achievement of Digital Population Identity in Sambas Regency has only reached around seven percent. This is yet to be in accordance with the government's mandate that the national target was 25 percent of the total population in December 2023; even in 2024, it is targeted to be 30 percent. The purpose of the research is to obtain an overview and analyze the innovation of IKD implementation at the Population and Civil Registration Office of Sambas Regency. The research method is quasi-qualitative. Researchers used semi-structured interviews, observation, and documentation. The results showed that the knowledge stage was shown through the socialization carried out by the Sambas Regency Population and Civil Registration Office through social media and ball pickup and the existence of clear procedures related to IKD activation. The persuasion stage is shown through the good attitude and response of the Sambas Regency Disdukcapil apparatus to follow up on IKD innovations. The decision stage is shown through the existence of good internal and external communication. The implementation stage shows that the development of achievements since the beginning of the implementation of IKD has not been significant due to the adjustment factor to its use in the community, especially for people who are elderly and technology illiterate. The confirmation stage is shown through the support of regional leaders in continuing the implementation of IKD innovations. However, there are still obstacles related to internet networks, especially in remote areas. In conclusion, the innovation of implementing the IKD application at the Population and Civil Registration Office of Sambas Regency is implemented quite well, and this is because of the five dimensions used; there are still two dimensions that require improvement, namely the Implementation and Confirmation dimensions.